The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/s1983-41952020000300003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pervious concrete focusing on non-destructive testing

Abstract: This study aims to investigate the properties of pervious concrete focusing on characterization tests by the Ultrasound Method. For this, three mixtures were produced with the paste/aggregate (P/Ag) ratio ranging from 0.45 to 0.65, water to cement ratio (w/c) of 0.3, and all the specimens were compacted with a steel rod. The application of the ultrasound method deserves special attention for the characterization of pervious concrete, due to a lack of research and the potential to develop analytical models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Consequentemente, a variedade de materiais de construção disponíveis, incluindo concreto, evoluiu significativamente e melhorou desde então (MARTINS FILHO et al, 2020). De acordo com Pils et al (2019), ao adicionar água a essa mistura, a mistura solta de cimento e agregados minerais se transforma em uma mistura mais espessa e sólida.…”
Section: Concreto: Conceitos Gerais E Definiçõesunclassified
See 1 more Smart Citation
“…Consequentemente, a variedade de materiais de construção disponíveis, incluindo concreto, evoluiu significativamente e melhorou desde então (MARTINS FILHO et al, 2020). De acordo com Pils et al (2019), ao adicionar água a essa mistura, a mistura solta de cimento e agregados minerais se transforma em uma mistura mais espessa e sólida.…”
Section: Concreto: Conceitos Gerais E Definiçõesunclassified
“…No entanto, sua resistência à tração é cerca de um décimo de sua resistência à compressão. Assim, para melhorar a sua resistência à tração é reforçado com aço, o que cria uma forte ligação com o concreto (MARTINS FILHO et al, 2020;PALMA;SOUZA, 2021).…”
Section: Concreto: Conceitos Gerais E Definiçõesunclassified
“…The properties of pervious concrete are studied by Filho et al [38], focusing on UPV. Three pervious concrete mixes were poured, with a binder-to-aggregate (B/Ag) ratio varying from 0.45 to 0.65 and a water-to-cement ratio (w/c) of 0.3.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the permeability is quantified by performing falling and/or constant head tests, while destructive testing is commonly utilized to evaluate the strength of PC ( 13 ). With recent technological advances, some researchers have also focused on utilizing simple and cost-effective nondestructive methods such as ultrasonic pulse velocity (UPV) ( 14 16 ), which is commonly used to assess the quality of traditional concrete. A study showed that the correlations between UPV and PC characteristics were not very strong ( 17 ), while others have reported that UPV presents fairly strong correlations with PC properties ( 16 ).…”
mentioning
confidence: 99%
“…With recent technological advances, some researchers have also focused on utilizing simple and cost-effective nondestructive methods such as ultrasonic pulse velocity (UPV) ( 14 16 ), which is commonly used to assess the quality of traditional concrete. A study showed that the correlations between UPV and PC characteristics were not very strong ( 17 ), while others have reported that UPV presents fairly strong correlations with PC properties ( 16 ). Another piece of research proposed statistical models to predict the compressive strength and hydraulic conductivity of PC ( 18 ).…”
mentioning
confidence: 99%